Behavior and Bio-Interactions of Anthropogenic Particles in Marine Environment for a More Realistic Ecological Risk Assessment - Corsi, Ilaria; Bergami, Elisa; Grassi, Giacomo (Frontiers in Environmental Science, 2020)
Due to production, usage and disposal of nano-enabled products as well as fragmentation of bulk materials, anthropogenic nanoscale particles (NPs) can enter the natural environment and through different compartments (air, soil and water) end up into the sea. With the continuous increase of production and associated emissions and discharges, they can reach concentrations able to exceed toxicity-thresholds for living species inhabiting marine coastal areas. Behavior and fate of NPs in marine waters are driven by transformation processes occurring as a function of NP intrinsic and extrinsic properties in the receiving seawaters. All those aspects have been overlooked in ecological risk assessment. This review critically reports ecotoxicity studies in which size distribution, surface charges and bio-nanointeractions have been considered for a more realistic risk assessment of NPs in marine environment. Two emerging and relevant NPs, the metal-based titanium dioxide (TiO2), and the polystyrene (PS), a proxy for nanoplastics, are reviewed and their impact on marine biota (from planktonic species to invertebrates and fish) discussed as a function of particle size and surface charges (negative vs positive) which affect their behavior and interaction with the biological material. Uptake of NPs is related to their nanoscale size, however in vivo studies clearly demonstrated that transformation (agglomerates/aggregates) occurring in both artificial and natural seawater drive to different exposure routes and biological responses at cellular and organism level. Adsorption of single particles or agglomerates onto the body surface or their internalization in feces can impair motility and affect sinking or floating behavior with consequences on population and ecological function. Particle complex dynamics in natural seawater is almost unknown although it determines the effective exposure scenarios. Based on the latest predicted environmental concentrations for TiO2 and PS NPs in the marine environment, current knowledge gaps and future research challenges encompass the comprehensive study of bio-nano interactions. As such, the analysis of NP biomolecular coronas can enable a better assessment of particle uptake and related cellular pathways leading to toxic effects. Moreover, the formation of an environmentally-derived corona (i.e. eco-corona) in seawater accounts for NP physical-chemical alterations, rebounding on interaction with living organisms and toxicity.